Complete mitochondrial genome of the green-lipped mussel, Perna canaliculus (Mollusca: Mytiloidea), from long nanopore sequencing reads. Issue 1 (2nd January 2018) - Ranjard, Louis; Wong, Thomas K. F.; Külheim, Carsten; Rodrigo, Allen G.; Ragg, Norman L. C.; Patel, Selina; Dunphy, Brendon J.
Abstract: We describe here the first complete genome assembly of the New Zealand green-lipped mussel, Perna canaliculus, mitochondrion. The assembly was performed de novo from a mix of long nanopore sequencing reads and short sequencing reads. The genome is 16, 005 bp long. Comparison to other Mytiloidea mitochondrial genomes indicates important gene rearrangements in this family.